Impact of Palivizumab on RSV Hospitalizations for Children with Hemodynamically Significant Congenital Heart Disease - Chang, Ruey-Kang R. (Springer-Verlag, 2009)
The objective of this study was to evaluate the impact of palivizumab prophylaxis on respiratory syncytial virus (RSV) hospitalizations among children with hemodynamically significant congenital heart disease (CHD). In 2003, the American Academy of Pediatrics (AAP) revised the bronchiolitis policy statement and recommended the use of palivizumab in children <24 months old with hemodynamically significant CHD (HS-CHD). California statewide hospital discharge data from years 2000–2002 (pre-AAP policy revision) were compared to those from years 2004–2006 (post-AAP policy revision). Hospitalizations due to RSV bronchiolitis for children <2 years of age were identified by IDC-9 CM codes 4661.1, 480.1, and 079.6 as the Principal Diagnosis. Children with CHD and children with HS-CHD were identified by the codiagnoses. The overall RSV hospitalization rate was 71 per 10,000 children <2 years of age. Of all RSV hospitalizations, 3.0% were among children with CHD, and 0.50% among children with HS-CHD. HS-CHD patients accounted for 0.56% of RSV hospitalizations in 2000–2002, compared to 0.46% RSV hospitalizations in 2004–2006. That represents a 19% reduction in RSV hospitalizations among HS-CHD patients after 2003. The 19% decrease in RSV hospitalizations equates to seven fewer hospitalizations (76 hospital days) per year among HS-CHD patients. We conclude that, since the recommendation of palivizumab for children with HS-CHD in 2003, the impact on RSV hospitalizations in California among HS-CHD patients has been limited. Considering the high cost of palivizumab administration, the cost-benefit of RSV prophylaxis with palivizumab warrants further investigation.